Study of Some Results on the Factor Group - Amer Khrija Abed (Mathematical Statistician and Engineering Applications, 2022)
The main goal of this paper is to calculate the cyclic decomposition of the finite commutative factor group , where , are distinct primes for all i = 1, 2, 3, …, m and are positive integers then: We have found the general irreducible characters table of the group .